The Tradition Ngejalang As a Basis for Moderation in Religious Practices in Lampung - Khoiruddin; Juhrotul Khulwah; Susi Nurkholidah; Hasanuddin Muhammad (International Journal of Community Engagement Payungi, 2024)
Ngejalang is a culture of praying together at cemeteries before the month of Ramadan and Eid al-Fitr which is held in Lampung. Ngejalang  is an expression of gratitude, a reminder of death, and a place for friendship between traditional leaders (clans) and the community. This tradition is a combination of religious and cultural values, and is maintained in Lampung, especially on the West Coast. This research aims to analyze the religious and socio-cultural functions of traditions wandering around for the people of Lampung, and analyzing the values of moderation in religious practices in tradition wandering around for the people of Lampung. The research was conducted on the West Coast of Lampung, data was collected by means of interviews and documentation. Tradition wandering around in Lampung it cannot be separated from religious values (worship), educational values (akhlak), social values (ukhuwah) and cultural values. This accommodating attitude towards traditions leads to an inclusive and tolerant religious attitude and creates a peaceful and dynamic atmosphere of religious life, so that traditions wandering around moderation capital in religious practices in Lampung.